Theoretical Study of Sulfur-containing Compounds Adsorption on Transition Metals (V, Ni, Co, Fe) Doped NbS2 Surface for Hydrodesulfurization Reaction - Suparada Kamchompoo (Science Faculty of Chiang Mai University, 2020)
The HDS reaction is one of the most important hydrotreating processes in petroleum refineries that use for removal of sulfur (S) compound from the crude oil. In this work, the adsorption of thiophene (C4H4S), benzothiophene (C8H6S), and hydrogen sulfide (H2S) on pure and transition metals (V, Ni, Co, Fe) doped niobium sulfide (NbS2) surface were investigated by density functional theory (DFT) calculations to further investigate the HDS reaction mechanism of S-containing compounds on this surface. The results show that in all case, the H2S, C4H4S and C8H6S preferred to adsorb on the metal edge sites (M-edge) of V doped NbS2 (V/NbS2) surface with adsorption energies (Eads) of -0.80, -0.79 and -1.38 eV, respectively. It was found that the C8H6S shows strongest adsorption energy because it exhibits significantly stronger π-interaction between C8H6S and V/NbS2 surface, compared to others. The understanding gained in the current study might be helpful in the development of active catalysts for the HDS reaction of S-containing compounds in petroleum oil production.